2017
DOI: 10.1155/2017/1406726
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl Trisulfide Suppresses Oxidative Stress‐Induced Activation of Hepatic Stellate Cells through Production of Hydrogen Sulfide

Abstract: Accumulating data reveal that garlic has beneficial effects against chronic liver disease. We previously reported that diallyl trisulfide (DATS), the primary organosulfur compound in garlic, reduced fibrosis and attenuated oxidative stress in rat fibrotic liver. The present study was aimed at elucidating the underlying mechanisms. The primary rat hepatic stellate cells (HSCs) were cultured and stimulated with hydrogen peroxide (H2O2) for inducing HSC activation under oxidative stress. We examined the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In the pathological process of hepatic fibrosis, it is well accepted that activated hepatic stellate cells (HSCs) is fundamental for the overproduction of extracellular matrix (ECM) in hepatic interstitium, thus resulting in hepatic fibrosis [82] . Current evidence suggests that inactivation of HSCs is an important mechanism for H 2 S to prevent and treat liver fibrosis [83] . However, a recent report has illustrated that the H 2 S production and CSE expression are incremented during HSC activation, and exogenous H 2 S promotes the proliferation of HSCs and evokes the fibrotic maker expressions of HSCs [84] .…”
Section: Role Of H 2 S In Liver Fibrosismentioning
confidence: 99%
“…In the pathological process of hepatic fibrosis, it is well accepted that activated hepatic stellate cells (HSCs) is fundamental for the overproduction of extracellular matrix (ECM) in hepatic interstitium, thus resulting in hepatic fibrosis [82] . Current evidence suggests that inactivation of HSCs is an important mechanism for H 2 S to prevent and treat liver fibrosis [83] . However, a recent report has illustrated that the H 2 S production and CSE expression are incremented during HSC activation, and exogenous H 2 S promotes the proliferation of HSCs and evokes the fibrotic maker expressions of HSCs [84] .…”
Section: Role Of H 2 S In Liver Fibrosismentioning
confidence: 99%
“…Polysulfanes have also been investigated as potent H 2 S donors in the presence of thiols [ 84 , 85 ]. Preclinical studies have shown that enhancement of endogenous H 2 S has an impact on vascular reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…It signifies that a decrease in the BDNF, H 2 S, and Nrf2 levels may contribute to the pathogenesis of neuropathic pain, while their restoration in the presence of diallyl sulfide and triallyl sulfide may possibly contribute in attenuating neuropathic pain. Diallyl sulfide and triallyl sulfide are reported to release H 2 S endogenously, and the usefulness of diallyl sulfide and triallyl sulfide in a number of diseases has been attributed to an increase in H 2 S levels [29,30]. Moreover, there have been studies showing that H 2 S donors may contribute in ameliorating neuropathic pain [31].…”
Section: Discussionmentioning
confidence: 99%